Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Is there any way I can simplify this sigma notation?

$$\begin{align*} \sum_{k=1}^m(5^k) \end{align*}$$

share|cite|improve this question

closed as off-topic by alexqwx, Gina, Tomás, leo, Stahl Aug 6 '14 at 20:27

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – alexqwx, Gina, Tomás, leo, Stahl
If this question can be reworded to fit the rules in the help center, please edit the question.

This is simply a geometric sum: $$\sum_{k=1}^m x^k = x\cdot \frac{1-x^{m}}{1-x}$$ – Joel Aug 6 '14 at 12:58
up vote 11 down vote accepted

Yes, there is.

Let $S = \displaystyle\sum_{k=1}^{m} 5^{k}$ be the sum you're trying to simplify, then you'll have $$5S=\color{red}{5^2+5^3+\cdots+5^m}+5^{m+1}$$ $$S=5^1+\color{red}{5^2+\cdots+5^{m-1}+5^m}$$ Then, substracting $S$ from $5S$ gives you $$4S=5^{m+1}-5^1\iff S=\frac{5^{m+1}-5}{4}.$$

In general, for $a\not =1$, you'll get the following using the above method : $$\sum_{k=1}^{m}a^k=\frac{a^{m+1}-a}{a-1}.$$ Note that if $a=1$, then $\sum_{k=1}^{m}1^k=m$ trivially.

share|cite|improve this answer
@Ogen: I hope this helps:) – mathlove Aug 6 '14 at 18:23
@EvanW: Thanks:) better now. – mathlove Aug 6 '14 at 18:53
thanks, your answer is a good demonstration. – Evan W Aug 6 '14 at 18:55
@mathlove I believe your last statement is incorrect; if $a = 1$, then $a - 1 = 0$, so the sum would be $\infty$; this is because $aS - S = (a - 1)S = 0\times S = 0$, so then you cannot actually solve for $S$. – feralin Aug 6 '14 at 19:16
@feralin: I edited it. That's what I meant. – mathlove Aug 6 '14 at 19:18

Using the formula $$\sum_{k=0}^{N} x^k=\frac{x^{N+1}-1}{x-1}$$ we have:

$$\sum_{k=1}^m 5^k=\sum_{k=1}^m 5^k+5^0-5^0=\sum_{k=0}^m 5^k-1=\frac{5^{m+1}-1}{5-1}-1=\frac{5^{m+1}-1}{4}-1=\frac{5^{m+1}-1-4}{4}=\frac{5^{m+1}-5}{4}$$

share|cite|improve this answer


It is a GP with first term=$5$ and common ration=$5$

share|cite|improve this answer

Not the answer you're looking for? Browse other questions tagged or ask your own question.